BOARD CHARACTERISTICS AND AUDIT QUALITY OF LISTED CONSUMER GOODS FIRMS IN NIGERIA - Aliyu Shehu Usman; Danson Andrew Gyar; Abdullahi Bala Ado (Gusau Journal of Accounting and Finance)
The study investigates the effects of board characteristics on the audit quality of publicly traded listed consumer goods firms in Nigeria from 2013 to 2022. An ex-post facto research approach was used in this study. For data analysis, the panel regression technique was used in the study. The study's findings revealed that board independence and board financial expertise have a positive and significant effect on the audit quality of Nigerian listed consumer goods companies. However, board gender diversity had a negative and insignificant effect on the audit quality of Nigerian-listed consumer goods companies. The study concludes that boards with more independent members who are not influenced by management may improve the audit process efficacy. To improve audit quality, listed consumer goods firms should focus on retaining board independence and guaranteeing the presence of directors with significant financial experience. While the relationship between board gender diversity and audit quality is still uncertain, it is critical to promote diversity and inclusivity on corporate boards in order to build a more robust governance structure. Continuous monitoring and research in this area will contribute to a better understanding of the relationship between gender diversity and audit quality.